BioEnterics Intragastric Balloon (BIB) versus Spatz Adjustable Balloon System (ABS): Our experience in the elderly. (February 2017) - Russo, Teresa; Aprea, Giovanni; Formisano, Cesare; Ruggiero, Simona; Quarto, Gennaro; Serra, Raffaele; Massa, Guido; Sivero, Luigi
Abstract: The BioEnterics Intragastric Balloon (BIB) and the Spatz Adjustable Balloon System (ABS) are in fact recommended for weight reduction as a bridge to bariatric surgery. We retrospected studied patients with body mass index (BMI) and age ranges of 37–46 and 70–80 years, respectively, who had undergone BIB from January 2010 to July 2012 and prospected studied patients who had undergone Spatz balloon from July 2012 to August 2014. The aim of this study is to compare BIB and Spatz in terms of weight loss, complications, and maintenance of weight after removal. For both procedures, the median weight loss was 20 ± 3 kg, median BMI at the end of the therapy was 32 ± 2, and no severe complication occurred.